Faktor Yang Berkontribusi Terhadap Kejadian Diabetes Mellitus Pada Usia Produktif: Diabetes Mellitus - Ismail, ismail (Jurnal Kesehatan, 2023)
Diabetes Mellitus (DM) is a dangerous disease that affects many people throughout the world. DM can infect both young and old people. This study aims to carry out further analysis of the contributing factors (gender and occupation, obesity, smoking) to the incidence of diabetes in productive age at the Andalas Health Center, Makassar City. This type of research was quantitative using a case control study design. The sample size was 30 case respondents and 30 control group respondents using a non-probability sampling technique, purposive sampling type. Data collection was carried out by giving questionnaires to patients who came to visit the Community Health Center. Men have a greater chance of developing DM based on an Odd Ratio (OR) of 1,511 and the chi square test results describe a correlation between gender and the incidence of DM p=0,032. There is no relationship between work and the incidence of DM p-value (0,273) p > 0,05 and Odd Ratio value 0,545. Obese people have a greater chance of developing DM with an Odd Ratio (OR) value of 3,143 times and the results of the chi square test, both of which show a significant correlation with a p-value of 0,000. The relationship between smoking factors and the incidence of DM showed a significant value (0,000) p <0,05. People who smoke have an Odds Ratio (OR) chance of developing diabetes of 9,750 times. Diabetes mellitus (DM) is influenced by several factors, such as gender (male), obesity, and smoking habits. Although work was not identified as a contributing factor, knowledge of these factors can be an important guide in providing optimal health services to DM patients.